THE ROLE OF COMMUNICATION IN THE MARKET RESEARCH PROCESS (Heritage, 2023)
Through communication, man initiates creativity, develops ideas, and exchanges information, makes acquaintances and affects the world spatially and temporally. Good communication is the key to success and is very important for the survival and development of any company. Communication is one of the key elements in market research for the reason that access to information and research methods are largely dependent on techniques and methods of business communication. An efficient and effective business communication has essential importance for the success of companies in today's business environment. The aim of this work is to determine the role of communication in the market research process through analysis and research.
Keywords: business communication, market, research process, research methodology, sources